Effectiveness of non-pharmacological pain management for severe symptoms in primary dysmenorrhea in sport - Kozłowska, Jana; Gołąbek, Zofia; Szymczyk, Simone; Król, Kacper; Jóźwiak, Sabina; Nowosielska, Julia; Jaczewska, Katarzyna; Barczuk, Patryk; Rejmer, Aleksandra; Lech, Jakub (Quality in Sport, 2026)
Background: Primary dysmenorrhea predominantly affects young women, significantly impacting their well-being, quality of life, psychological and sexual health, as well as other aspects of daily functioning. This condition manifests primarily as severe menstrual pain in the absence of an identifiable organic pathology. Aim: This narrative review evaluates the available treatment options for primary dysmenorrhea. Our aim was to synthesize and critically analyze the existing evidence on the effectiveness of various pain management strategies for severe symptoms of primary dysmenorrhea to inform clinical practice. Methods: To assess the efficacy of pain management in severe primary dysmenorrhea, we conducted a systematic literature review using databases including PubMed, ScienceDirect, ResearchGate, and Google Scholar. We included randomized controlled trials (RCTs), cohort studies, and case-control studies published between 2022 and 2025. Data were extracted and categorized in tables based on different characteristics. Results: Physical therapy, acupuncture, herbal remedies, relaxation techniques, and psychotherapy demonstrated potential as complementary therapies. A personalized, multimodal approach integrating multiple interventions may yield superior outcomes. Conclusion: Non-pharmacological therapies are effective in managing primary dysmenorrhea. Adjunctive interventions such as physical therapy, acupuncture, herbal medicine, relaxation techniques, and psychotherapy may enhance treatment outcomes.